Protection of floating photovoltaic structures in coastal waters - Onn, Shi Ee (Nanyang Technological University, 2022)
Due to the growing need for renewable energy sources and the limited availability of land, floating solar farms are an effective solution to mitigate the problems mentioned above. Floating solar farms are solar panels installed on the surface of lakes, reservoirs, or coastal areas. Singapore, an island country, has resorted to using the nearby waterways to increase solar energy production. Last year, Singapore unveiled one of the world’s largest floating solar farms at Tengeh Reservoir spanning 45 hectares. Since they can be installed in coastal areas, floating solar farms must be protected against wave motion, which can lower their efficiency and put maintenance workers at risk. This study investigates polypropylene (PP) sheets acting as a breakwater for floating structures with the effect of 3 parameters namely: porosity, surface penetration of vertical sheet and tension. Experiments were carried out in a wave flume simulating regular waves with 10 wave periods. The amplitudes of the waves were measured by ultrasound sensors. The reflection and transmission coefficients were obtained using MATLAB, and the results were then utilized to calculate the energy dissipation percentage. The results indicated that porosity has the greatest influence on wave attenuation because increased porosity results in lower reflection and higher transmission coefficient, while tension and surface penetration have little impact on the effectiveness of the wave barrier.